Odpowiedź: Zad1. (4x-2y+1)-(x-y)+(y-2x)= (4x-2y+1)-(x+y)+(y-2x)=1+1x+4y
Zad2. (a-4b)-(4+3a)-(3b-7)= ((-1 -4•3)-(4-3•(-1))= ((-1)-12)-(4-(-3))= 13-7=6
Zad 3. 2-y+2x= 2-0,1+2•(-1,6)= 1,9+(-3,2)= -1,3
Zad 4. x+8=9x:5= 1,9x
Zad 5. 4(y+2)-3(y-2)= 4•(y+2)-3•(y-2)= 4•3y-3•y=12y-3y= 9y
Zad 6. 4(2x - 3y) =4•2x-3y=8x-3y
Zad 7. (5k+n)(x-2y)-2k(3y-x)=3k+n-x+6y
Zad 8. 2a - 3b + 3a - 2b =5a+5b
Zad 9. 10 - (6x + 3) =10-3 -6x = 7-6x
Zad 11. (4a + 2)(2b - 3) =4a-1+2b
Szczegółowe wyjaśnienie: Nie wiem czy dobrze ale próbowałam :))